Crimean Hemorrhagic Fever: Ecologic and Epizootic Role of the Corvidae Family - S. Yu. Vodyanitskaya (Проблемы особо опасных инфекций, 2008)
The role of birds in the circulation of the virus of Congo-Crimean hemorrhagic fever (CCHF) is described in the paper. Investigation of 758 samples of birds revealed the virus CCHF antigen to be present in 19 (2.51 % ± 0.57) rooks' samples. Corvidae were shown to be a full-fledged co-member of the Crimean hemorrhagic fever (CHL) natural foci in the territory of Rostov Region. Epidemiologic significance of this bird family consists in dissemination of the CCHL virus, expansion of the existing natural CHL foci, and thereby supporting the formation of new ones. Ecologic and epizootiologic role of Corvidae should be taken into consideration while conducting epidemiologic surveillance in HCL natural foci.